2008
DOI: 10.1007/s10602-008-9049-1
|View full text |Cite
|
Sign up to set email alerts
|

Constitutions and economic reforms in transition: an empirical study

Abstract: Constitutional economics, Post-socialist transition, Economic reforms, H11, K19, P21, P26,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…, 1999). In line with that, Metelska‐Szaniawska (2009) found that constitutional quality has a positive influence on reform progress in post‐socialist countries. Although these findings are compatible with the general literature on the relationship between democracy and liberalization (see, for example, De Haan and Sturm, 2003; Pitlik, 2007; Rigobon and Rodrik, 2005), the evidence for the post‐socialist countries is still based on just a few investigations, most of which are not very recent.…”
Section: Relating Democracy and Prosperity In The Literature: Theosupporting
confidence: 68%
“…, 1999). In line with that, Metelska‐Szaniawska (2009) found that constitutional quality has a positive influence on reform progress in post‐socialist countries. Although these findings are compatible with the general literature on the relationship between democracy and liberalization (see, for example, De Haan and Sturm, 2003; Pitlik, 2007; Rigobon and Rodrik, 2005), the evidence for the post‐socialist countries is still based on just a few investigations, most of which are not very recent.…”
Section: Relating Democracy and Prosperity In The Literature: Theosupporting
confidence: 68%
“…A score of zero implies a strong presidential system, two a pure parliamentary system, with scores between 0 and 2 representing mixed systems. In the far right column are the classifications of Metelska‐Szaniawska () based on a careful reading of each country's constitution. The two classifications are in substantial agreement.…”
Section: What Has Happened?mentioning
confidence: 99%
“…See, Johnson, Kaufmann, and Shleifer (), Metelska‐Szaniawska () for transition countries, and the survey by De Haan, Lundström and Sturm ().…”
mentioning
confidence: 99%
“…The constitution is a supreme legal act which stipulates the fundamental principles of the system adopted by the state (MetelskaSzaniawska, 2009). After the downfall of socialism, the state cannot function on the basis of a socialist constitution in the capitalist environment (Metelska-Szaniawska, 2009). In this case, Tanzania has not completed the transition because transition ends when a complete break with the past is reached (Buyandelgeriyn, 2008).…”
Section: 2mentioning
confidence: 99%